1994
DOI: 10.3354/meps107103
|View full text |Cite
|
Sign up to set email alerts
|

Copepod predation on phagotrophic ciliates in Oregon coastal waters

Abstract: Clearance rates on natural assemblages of aloricate, phagotrophic ciliates (20 to 100 pm) were measured for calanoid copepods in Oregon, USA, coastal waters. Experiments were conducted prior to and throughout the 1991 upwelling season in an effort to determine the trophic significance of cihates as copepod prey in a system often dominated by large phytoplankton. Copepods cleared ciliates at higher rates than they cleared phytoplankton, except during upwelling-induced diatom blooms. Clearance rates on ciliates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
89
3
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(103 citation statements)
references
References 27 publications
7
89
3
2
Order By: Relevance
“…10). Some studies suggest that the effects of micrometazoans grazing on phytoplankton may be mediated mostly by their control of microzooplankton populations (Fessenden and Cowles 1994). However, our results indicate that their grazing pressure on protozoans appeared to be modest in agreement with other previous studies for mesozooplankton (Broglio et al 2004).…”
Section: Copepod Naupliicontrasting
confidence: 48%
“…10). Some studies suggest that the effects of micrometazoans grazing on phytoplankton may be mediated mostly by their control of microzooplankton populations (Fessenden and Cowles 1994). However, our results indicate that their grazing pressure on protozoans appeared to be modest in agreement with other previous studies for mesozooplankton (Broglio et al 2004).…”
Section: Copepod Naupliicontrasting
confidence: 48%
“…Although microzooplankton might contribute less than phytoplankton to mesozooplankton diets in terms of ingestion rates in rich food conditions (Calbet and Saiz, 2005;Liu et al, 2005b), our result suggested that carnivorous feeding was always a reason for the reduction of the clearance rate of phytoplankton by mesozooplankton assemblage even during phytoplankton bloom in addition to functional response. Preference on microzooplankton by copepods during phytoplankton bloom and associated trophic cascades were also reported in other coastal and estuarine waters (e.g., Fessenden and Cowles, 1994;Liu et al, 2005a).…”
Section: The Effect Of Mesozooplankton Carnivorymentioning
confidence: 97%
“…It has been reported by many field studies that when omnivorous species dominate in assemblage, mesozooplankton or copepods (a major group of mesozooplankton) often prefer feeding on microzooplankton to phytoplankton due to larger sizes and higher nutritional quality of microzooplankton (e.g., Stoecker and Capuzzo, 1990;Gifford, 1991;Fessenden and Cowles, 1994;Atkinson et al, 1996;Nejstgaard et al, 2001;Zeldis et al, 2002;Calbet and Saiz, 2005;Liu et al, 2005b;Gifford et al, 2007). Predation on microzooplankton is also an important feeding strategy of omnivorous species that are able to switch their feeding behaviors to conquer food limitation or to survive during nuisance phytoplankton blooms in coastal waters (Kiørboe et al, 1996;Nejstgaard et al, 1997;Gifford et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Because nonpigmented ciliates and heterotrophic dinoflagellates are generally available, and even preferred, as prey by copepods (Stoecker and Capuzzo 1990;Kleppel 1993;Fessenden and Cowles 1994;Suzuki et al 1999;Levinsen et al 2000;Nejstgaard et al 2001), the ability to directly investigate feeding on nonpigmented organisms by copepods is of considerable importance. Yet, current methodological limitations hamper our ability to quantify Estimated time for 50% gut evacuation was 14.4 min at 5°C; P(x) = P 0 × exp (-k × x) , P 0 = 11.4; SE = 1.1; P < 10 -4 ; k = 0.048; SE = 0.008; P < 10 -4 ; r 2 = 0.86; df = 18.…”
Section: Discussionmentioning
confidence: 99%